Diarrheal prevalence and risk factors among under five years children in remote coastal area of Bangladesh (Asian-Australasian Journal of Food Safety and Security, 2018)
Diarrhea causes major childhood morbidity and mortality globally. This study aimed to investigate the prevalence and associated factors of childhood diarrhea among under-five children in Southern coastal area of Bangladesh. A community-based cross-sectional study conducted from April to June 2018 among 202 randomly selected children. A structured questionnaire used to collect information on a three month diseases occurrence and other covariates. The association of diarrhea with socio economy, personal and food hygiene practices observed using multivariate logistic regression after adjusting for potential confounders. Prevalence of childhood diarrhea was 10.9%. In bivariate analysis, mother’s education, family income, father’s occupation, hand washing of child before feeding and refrigerator associated with outcomes. In multivariate analysis, father’s occupation, hand washing of child by soap before feeding and having refrigerator in households was associated with childhood diarrhea after controlling the socio-demographic factors (age and gender). Child of unemployed fathers were more likely to have diarrhea than employed father (AOR=0.206; 95% CI: 0.070-0.610).Child do not wash hand before feeding (AOR=0.393; 95% CI =0.102-0.511) and households not having refrigerator (AOR= 0.072; 95% CI: 0.007-0.745) had higher odds of diarrhea. The load of diarrhea in this setting was almost double to the national rate. Poor hand washing of child and refrigerator are major risk factor high burden of the disease. Health promotion strategies on proper food storage and child feeding practices are recommended for the prevention of childhood diarrhea.Asian Australas. J. Food Saf. Secur. 2018, 2(2), 93-99